1979
DOI: 10.1093/nar/6.8.2787
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the protection of specific RNA sequences in globin messenger ribonucleoprotein particles

Abstract: Purified 15 S globin mRNA-protein (mRNP) complexes obtained by EDTA dissociation of duck reticulocytes polyribosomes were digested with the calcium dependant Staphytococcus auLeuz nuclease (EC 3. 1. 4. 7.). 25 % of the globin mRNA sequences were resistant to extensive nuclease digestion as determined by TCA precipitation of the digested 15 S particles labelled in vivo with tritiated uridine.Polyacrylamide gel electrophoresis of the RNA from nuclease digested 15 S particles showed that the protected oligoribonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We have recently shown that in 15 S duck globin mRNP, 25 % of the mRNA sequences are protected by proteins against staphylococcal nuclease digestion, and that proteins interact non-randomly with the mRNA sequences, protecting specific mRNA fragments (22). Similar results were obtained for nuclear pre-mRNP particles (23).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…We have recently shown that in 15 S duck globin mRNP, 25 % of the mRNA sequences are protected by proteins against staphylococcal nuclease digestion, and that proteins interact non-randomly with the mRNA sequences, protecting specific mRNA fragments (22). Similar results were obtained for nuclear pre-mRNP particles (23).…”
Section: Introductionsupporting
confidence: 59%
“…Fingerprint analysis : Electrophoresis in first dimension was on cellulose acetate strips at 4,000 volts for 60 minutes using a buffer containing 5 % acetic acid, 2 mM EDTA, 7 M urea adjusted to pH 3.5 with pyridine. Second dimension analysis was homochromatography on DEAE-cellulose thin layer plates using homomixture C, 650 C, 6 hours, as described previously (22), according to Brownlee's procedure (25). Affinity chromatography : mRNA was chromatographed on oligo-(dT)-cellulose as described by others (26)(27), with the difference that binding of poly(A+)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelling was carried out with 32P-labelled pCp in a reaction catalyzed by T4 RNA ligase according to Peattie (1979). Enzymatic digestion of ScRNA with RNAse Tl was performed as described earlier (Goldenberg et al, 1979). Electron microscopy A drop of the appropriate sucrose gradient fractions (cf., Figure 1) was put onto freshly glow-discharged and carbon-coated copper grids.…”
Section: Rna Fingerprintingmentioning
confidence: 99%
“…All types of RNA in the cell are covered by proteins (1:3 ratio in mRNPs). In the case of mRNA, it was shown by electron microscopy (Dubochet et al , 1973) that proteins are aligned along the entire length of the RNA molecules (and it is thus likely also for pre‐mRNA), protecting specific oligomotifs from degradation by RNase (Goldenberg et al , 1979). Only in rare cases the oligonucleotide sequence that binds a given regulatory protein is known; in addition to the poly(A)‐binding protein (PABP), one might mention, for example, the IRE‐BP (iron response element binding protein), a protein that binds an oligomotif in the 5′‐side or 3′‐side UTR of the mRNAs for ferritin and transferrin, respectively (Thomson et al , 1999).…”
Section: The Transgenonmentioning
confidence: 99%